Task Based Learning On English Reading Skill Of Tenth Grade Class At SMAN 1 Negara - Ayu Putu Yulyana Anjani; Ni Luh Nyoman Seri Malini; Ketut Artawa (Jurnal Riset Rumpun Ilmu Bahasa, 2025)
This study investigated the implementation and effectiveness of Task-Based Language Teaching (TBLT) in enhancing the English reading skills of tenth-grade students at an Indonesian senior high school. The research was motivated by the persistent gap left by traditional language teaching methods, which frequently emphasize grammatical accuracy and vocabulary memorization while often neglecting the development of practical reading abilities. To address this issue, the study systematically examined the application of TBLT through three structured phases: pre-reading, main reading, and post-reading tasks. Each phase was designed to promote active learning, critical thinking, and student engagement in the reading process. The methodology involved classroom observations, task-based instructional activities, and an analysis of student exam scores as the primary indicators of progress. During the pre-reading phase, students were encouraged to activate prior knowledge and predict content, which helped build contextual understanding. In the main reading phase, tasks focused on developing essential reading strategies such as skimming for general ideas and scanning for specific information.